The Gulag Archipelago: From Inferno to Paradiso - David Matual (Studies in 20th & 21st Century Literature, 1982)
It is apparent from the title of his novel The First Circle and from various details there and in other works that Alexander Solzhenitsyn is familiar with at least the imagery of Dante's Divine Comedy. One direct and several indirect references to it also suggest a Dantean subtext in his longest and most ambitious project, The Gulag Archipelago. Indeed, the loci of the Comedy—Inferno, Purgatorio, and Paradiso—are transformed in the Gulag into metaphorical representations of the various stages in the development of man's consciousness—and especially Solzhenitsyn's consciousness—during the ordeals of arrest, inquest, imprisonment, and exile. The Inferno is surely the most prominent and in some ways the most memorable part of Solzhenitsyn's work. It is the phase in which most of the zeks live—the phase of unremitting hatred, cynicism, and selfishness caused by the cruelty and degradation of their experiences in prisons and labor camps. It is a life among rapacious thieves and police informers, a life in which only the self matters. The Purgatorio is the stage reached by those who, like Solzhenitsyn himself, begin to question the validity of all ideologies and who recognize and admire the strength of those whose personality derives from an uncompromisingly spiritual worldview. But in the Purgatorio the light of understanding is just beginning to penetrate the darkness; the process of spiritual rebirth is in an embryonic state. When a zek crosses the threshold of the Paradiso (as Solzhenitsyn clearly does—notably in Part IV), he attains a wisdom and understanding not yet accessible to the majority of men. He realizes that attachments to property, possessions, and even loved ones only add to the sufferings of the prisoners. He now knows that the life of the spirit, divorced from earthly preoccupations, is the only life that is eternal and inviolate. With that realization he has achieved the ultimate knowledge and the ultimate happiness.
Keywords: Gulag Archipelago; The First Circle; Alexander Solzhenitsyn; Dante; Divine Comedy; Inferno; purgatorio; paradiso; metaphorical representation; metaphor; consciousness; zek; spirit; knowledge; happiness